Anti-inflammatory and anti-oxidative properties of cocoa ethanolic extract rich in polyphenols - Ranneh, Yazan (2014)
This study aimed to investigate the anti-oxidative and anti-inflammatory properties of ethanolic cocoa extract-rich in polyphenols in vitro. It is hypothesized that cocoa extract polyphenols may be benefit for diseases-related to chronic inflammation. The accumulation of macrophage, during the inflammatory state, plays a potent role in releasing pro-inflammatory markers. Additionally, the accumulation of free radicals along with inflammatory state is considered to be the initiative of several diseases such as cancer, atherosclerosis, diabetes and arthritis. Finding a potent agent suppressing the free radicals and pro-inflammatory markers is still required. Polyphenols have been thought to own strong anti-oxidative and anti-inflammatory characteristics. To confirm this assumption, the phenolic compounds of cocoa bean powder were isolated and identified by column chromatography and HPLC. Polyphenolic compounds were then characterized by HPLC-UV-/ESI-MS-MS. Five phenolic compounds were detected namely, catechine, epicatechine, gallic acid,cholorgenic acid and protocatechuic acid. In this study, the scavenging or the TAC (%) (Total Antioxidant Capacity) of cocoa polyphenol (CP) extract that contain 114.0 mg/g of gallic acid –equivalent phenolics and 94.3 mg/g catechin- equivalent flavonoids were also investigated. Their free radical-scavenging activity was assessed by DPPH (2,2-diphenyl-1-picrylhydrazyl) assay, β-carotene bleaching test,and XO (Xanthin Oxidase) inhibitory activity and compared with standard drugs (allopurinol) in different concentrations (5, 10, 20) mg/ml. TAC was further assessed by CP extract against the myoglobin-induced oxidation of ABTS (2,2'-azino-di(3-ethylbenzthiazoline-6-sulfonic acid) and expressed as Trolox equivalent in different concentration (100, 200, 300) μM/TE g. CP extract had significantly (P < 0.05) potential antioxidant activities with various concentrations. On the other hand, the anti-inflammatory activity of CP extract was assessed with their ability to inhibit the pro-inflammatory enzyme 5-lipooxygenase (5-LOX) using synthetic substrate (Soybean lipoxygenase) and mediators prostaglandin E2 (PGE2), Reactive Oxygen Species (ROS), Nitric Oxide (NO) and Tumor necrosis factor-alpha (TNF-α) using RAW264.7 cells sensitized by lipopolysaccharide (LPS). Our findings indicated that cocoa extract significantly produced inhibition against 5-LOX activity (P< 0.05). In addition, CP extract, in a dose-dependent manner, exhibited a high ability in suppressing the production of ROS, NO, TNF-α, and PGE2 in RAW 264.7 cells. Conclusively, our in vitro study suggest that the improvement of anti-oxidative and inflammatory state is a pivotal action of dietary polyphenols-derived from cocoa beans which in turn provide a rationale application in clinical nutrition practice for treatment of chronic diseases.